دراﺳﺔ اﻟﺘﺮﻛﯿﺐ اﻟﻜﯿﻤﯿﺎﺋﻲ وﻣﺤﺘﻮى ﺑﻌﺾ اﻷﺣﻤﺎض اﻷﻣﯿﻨﯿﺔ اﻷﺳﺎﺳﯿﺔ واﻟﻌﻨﺎﺻﺮ اﻟﻤﻌﺪﻧﯿﺔ واﻟﻔﯿﺘﺎﻣﯿﻨﺎتﻟﻠﺸﺎﻣﯿﺔ اﻟﻤﺒﺎﻋﺔ ﻣﺤﻠﯿﺎ (Journal of the College of Education for Women, 2019)
Pop corn forms appetizer wide use by different age groups in many occasions, especially the children of school age, so we went towards the study of its chemical composition ;determination the amount of calories processed; and its content of some essential amino acids and essential vitamins. Therefore we selected six samples of popcorn fromfive different areas belonging to Salah al- din province which are displayed in the local markets and prepared at the traditional way by the vendors by a preparation machines of popcorn.The results showed that the humidity content range was 12.0-13.8%, protein 7.6 - 10.1%, while each of fat and ash giving percentages ranged from 3.8 - 4.2% and 3.1 4.2%, respectively, carbohydrates were ranged from 69.4 -72.2%.A study of the content of some of the essential amino acids, which included methionin , cystin, lysine , arginine and tryptophan, showed that there range were 0.13-0.18 , 0.14-0.18 , 0.22-0.26 , 0.06-0.10 and 0.38 -0.41 g / 100 g nitrogen, respectively.The calculated amount of calories processed by eating 100 grams of popcorn ranged between 349.0 -358.2 Kcal. The determination of some essential minerals showed that there content were 25.3 – 30.6 mg of calcium, 0.56-0.76 mg of iron, 23.6 - 31.3 mg of manganese, 225.6-248.6 gm of phosphorus , 230.3 -245.6 gm of potassium, and 0.43-0.9 mg of zinc / 100 grams of popcorn. The assessment of some of the essential vitamins, including thiamine, riboflavin, niacin, pyridoxine, and folic acid showed that the content were 0.195-0.250 mg, 0.60-0.80 mg , 0.6-1.75 mg , 0.55-0.7 mg , 20.5- 23 mg / 100 g of popcorn respectively.